3D wind buckling analysis of steel silos with stepped walls. (September 2019) - Maleki, Shervin; Mehretehran, Alireza Moazezi
Abstract: Thin-walled cylindrical steel silos are one of the key structures for storage of materials in many industries and agricultural sectors. They are susceptible to instability under wind pressure when they are empty or partially filled. This paper investigates numerically the wind buckling behavior of three sample steel silos with stepped walls composed of isotropic rolled shells. Wind load vertical and circumferential distributions were adopted from Eurocodes. Two proposed circumferential pressure distributions for an isolated silo and a silo in a group with a closed roof were taken into consideration. Moreover, the effect of additional inward pressure, proposed by Eurocode, on buckling capacity of vented silos with a small opening was evaluated. Accordingly, comprehensive 3D finite element models were used and detailed linear and non-linear buckling analyses were conducted. The wind buckling capacity of sample structures considering multiple amplitudes of initial imperfections was also assessed. The results obtained suggest a considerable decrease in the buckling resistance of imperfect silos. Finally, Eurocode provisions for the wind buckling stress design of unstiffened cylinders with step-wise variable wall thickness were examined and the relevant conclusions have been made. Graphical abstract: Image 1 Highlights: Comprehensive FEM wind buckling assessments of three steel silos were conducted. Wind distributions for an isolated silo and a silo in a group were considered. Valuable insights into wind buckling of closed roof and vented silos were provided. Extensive imperfection sensitivity analyses were undertaken. Discharge buckling assessments of sample silos by GMNIA analysis were presented.